2018
DOI: 10.1016/j.jalz.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of demyelination in mild cognitive impairment and dementia using a direct and specific magnetic resonance imaging measure of myelin content

Abstract: We believe this to be the first demonstration of myelin loss in MCI, Alzheimer's disease, and vascular dementia using a method that provides a quantitative magnetic resonance imaging-based measure of myelin. Our findings add to the emerging evidence that myelination may represent an important biomarker for the pathology of MCI and dementia. This study supports the investigation of the role of myelination in MCI and dementia through use of this quantitative magnetic resonance imaging approach in clinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 59 publications
4
105
0
Order By: Relevance
“…We have previously used mcDESPOT MCR to characterize the spatiotemporal pattern of human brain myelination as reflected by MWF Deoni et al, 2016), and to explore the crosssectional relationships between MWF and cognitive development O'Muircheartaigh et al, 2014). In addition to pediatric applications, mcDESPOT has also been used to investigate myelin change in known white matter demyelinating and dysmyelinating disorders, for example, multiple sclerosis (Kitzler et al, 2012;Kolind et al, 2012;Kolind et al, 2013), Alzheimer's disease , and dementia (Bouhrara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously used mcDESPOT MCR to characterize the spatiotemporal pattern of human brain myelination as reflected by MWF Deoni et al, 2016), and to explore the crosssectional relationships between MWF and cognitive development O'Muircheartaigh et al, 2014). In addition to pediatric applications, mcDESPOT has also been used to investigate myelin change in known white matter demyelinating and dysmyelinating disorders, for example, multiple sclerosis (Kitzler et al, 2012;Kolind et al, 2012;Kolind et al, 2013), Alzheimer's disease , and dementia (Bouhrara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons why NYT can improve apathy remain to be clarified. Recent reports have revealed that myelin loss is an important factor in the pathology of MCI, as well as both degenerative and vascular dementia [9,10]. The association between demyelination and apathy has also been reported in multiple sclerosis patients [11,12].…”
Section: Discussionmentioning
confidence: 93%
“…In humans, partial loss of myelin, axons and oligodendroglial cells have been observed histologically in early AD (Brun and Englund, 1986;Englund et al, 1988;Kobayashi et al, 2002;Roher et al, 2002;Svennerholm and Gottfries, 1994). Recent non-invasive MRI methods including diffusion MRI and relaxometry also provide evidence for demyelination in mild cognitive impairment and early AD (Bouhrara et al, 2018;Dong et al, 2020). Current theories further suggest a two-step demyelination process, with initial oligodendrocyte degeneration releasing iron, which promotes amyloid plaques, which in turn further destroy myelin until the neurodegenerative stage (Bartzokis, 2011(Bartzokis, , 2004.…”
Section: Discussionmentioning
confidence: 99%